Cognitive radio oriented wireless networks : 13th EAI International Conference, CROWNCOM 2018, Ghent, Belgium, September 18-20, 2018, Proceedings /: 13th EAI International Conference, CROWNCOM 2018, Ghent, Belgium, September 18-20, 2018, Proceedings. (2019) - Unknown
No abstract available